2011
DOI: 10.1002/pssr.201105250
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of TiO2 and Al‐doped TiO2 films on Ir substrates for ultralow leakage currents

Abstract: Rutile structured TiO 2 , which has a dielectric constant value ~100 is attracting considerable interest as an alternative dielectric material for sub-30 nm technology dynamic random access memory capacitors [1][2][3][4]. Even though it is not the thermodynamically stable phase at the typical ALD temperature (<300 °C), in-situ formed thin RuO 2 layer induce the formation of rutile TiO 2 films on Ru substrates by atomic layer deposition (ALD) when using O 3 , O 2 or N 2 O plasma as the oxygen sources [1,2,5,6].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…It was recently reported that a very thin conducting layer interposed between a thicker metal electrode and an insulator layer does not realize the bulk work function of the thin conducting layer. 12 It is likely that the deterioration in the leakage properties of the ATO film on thinner Ru/TiN results from lowering the work function of the Ru layer through the influence of the lower TiN electrode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was recently reported that a very thin conducting layer interposed between a thicker metal electrode and an insulator layer does not realize the bulk work function of the thin conducting layer. 12 It is likely that the deterioration in the leakage properties of the ATO film on thinner Ru/TiN results from lowering the work function of the Ru layer through the influence of the lower TiN electrode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…13,14 Ir also forms IrO 2 , of which structure is also rutile forming the rutile phase TiO 2 on top, during the ALD of TiO 2 or ATO. 12 However, forming interfacial IrO 2 requires an extended O 3 pulse time, which is too long in order to make the ALD process practical. The Pt does not form any oxide, which is structurally compatible with the rutile TiO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deposition of TiO 2 on RuO 2 is not the only case for crystallinity coherency of dielectric with the electrode. As the same manner, IrO 2 , MoO 2 , and SnO 2 also can induce the rutile-phased TiO 2 thin film during the ALD process [50,75,76,77]. Consequently, using a substrate that has crystal structure coherency is one of the most effective ways of acquiring high dielectric constants in deposited dielectric thin films.…”
Section: Crystallinity Coherency With the Electrodementioning
confidence: 97%